Pengaruh suhu sintering terhadap sifat penyerap gelombang mikro dari nanokomposit CoFe2O4/PVDF yang di preparasi dengan metode sol-gel (Sintering temperature effect on the microwave-absorbing properties of the CoFe2O4 / PVDF nanocomposites prepared by the sol-gel method) - Yona Sri Mantia; - Ramli; Yenni Darvina; - Desnita (Department of Physics – Universitas Negeri Padang UNP, 2019)
This number applications of microwaves are numerous so that it produces microwaves that emit. If it is not in control, there will be interference with electromagnetic signals. This also causes disruption of the working system of the Neighborhood. CoFe2O4/PVDF nanocomposite synthesized by the sol-gel method for microwave preparation was completed. Making materials to absorb microwaves uses five variations of sintering temperature, namely 250℃, 280℃, 350℃, 400℃, and 450℃. The sintering process is carried out using a furnace. The presence of a single phase on CoFe2O4/PVDF nanocomposite was characterized using X-Ray Difraction (XRD), to see the functional groups using Fourier Transform Infrared (FTIR), and to help wave use carried out using Vector Network Analyzer (VNA). This study discusses the sintering of microwave absorbers.The characterization results using VNA get a maximum Reflection Loss value of -29,7051 dB at a temperature of 400℃, frequency of 11.76 GHz, with absoption coefficient 96%. Different sintering temperatures produce a large amount of different absorptions. Nanocomposite which has a large value of reflection loss does not necessarily have a large answering tape width. The quality of materials that are good for microwave absorbers must also consider the value of the width of the capture band.The best absorption occurs at a temperature of 450 ℃ because have a maximum reflection loss value -21.116 dB, frequency of 6.00 GHz, absorption band widht 0.54 GHz, and absoption coefficient 91%.